On the effects of heat process on the physical properties of rice - Zulkifli, Nur Saheirah (2020)
Four rice types such as Jasmine, basmati, brown and glutinous rice were observed for physical properties.Thereafter, the four rice types prepared by specific water to rice ratios during heat process were evaluated. The study focused on measuring the texture and color analyses of cooked rice.The result showed significance different color of L* lightness a* redness and b* yellowness between brown, basmati and Jasmine cooked rice but no significance different for glutinous cooked rice. In addition, the increase of water rice ratio resulted with decreases of lightness, redness and yellowness then induce greater color change, ∆E of brown, basmati, jasmine and glutinous rice. Furthermore, the textural analysis of rice types significantly lower on hardness, cohesiveness, chewiness, springiness and gumminess with different of water ratio. However, the result showed different significance on hardness of jasmine rice while , no significance hardness of basmati, brown and glutinous rice when replaced 3: 1 of water ratio during heating process.Lastly, the results provide an insight on new information to rice during cooking. Althougth, this research also provide scientific numerical data on what changes occurred during heat process.